Comparing hyperspectral reflectance characteristics of Caucasian bluestem and native tallgrass prairie over a growing season - Grabow, Bethany Susan Porter (Kansas State University, 2010)
Caucasian bluestem [Bothriochloa bladhii (Retz) S.T. Blake] is a perennial, C4 warm-season bunchgrass that was first introduced in 1929 from Russia as a potential forage crop in the Great Plains. Due to its invasiveness and tolerance of drought and grazing pressure, Caucasian bluestem can out-compete native prairie species. Research has shown that this species, when compared to native tallgrass species in the Flint Hills of Kansas causes decreased cattle weight gains because of its poor forage quality relative to tallgrass prairie species. Traditional methods of plant data measurements and mapping are costly and time consuming. Use of remotely sensed data to map and monitor the distribution and spread of this plant would be most useful in the control of this aggressive invader. Spectroradiometer data were collected over the 2009 growing season to determine if and when Caucasian bluestem was spectrally unique from native tallgrass prairie species. Observations were made from June through September as the plants were going into a senescent state. Reflectance data were measured approximately every two weeks or when clear/near clear sky conditions prevailed. Statistical analyses for differences in spectral characteristics were conducted to determine the optimal spectral bands, indices and timing for discriminating Caucasian bluestem from native tallgrass species. Difference in reflectance for spectral reflectance of bands 760 nm, 940 nm, 1,070 nm, and 1,186 nm were found to be statistically significant on the June 17th and June 30th sampling dates. The following band ratios and indices were found to be significantly different between Caucasian bluestem and native range on the June 17th collection date: Simple Ratio, Modified Normalized Difference Index, Normalized Phaeophytinization Index, Plant Index 1, Normalized Water Difference Index, Water Band Index, Normalized Difference Nitrogen Index, and the Normalized Difference Lignin Index. Findings of this study suggest that Caucasian bluestem can be spectrally discriminated from native tallgrass prairies of the Flint Hills in Kansas if the measurements are collected in mid to late June. Statistical analyses also showed differences between treatments for percent litter, grass, and forb basal cover.
Keywords: hyperspectral; Caucasian bluestem; reflectance; Agriculture, Agronomy (0285); Agriculture, Range Management (0777)